The challenges facedb by the ordinary level students in analysing poetry : a case study of Nkulumane High School in Bulawayo Province. - Mutandwa, Kundai (Midlands State University, 2020)
The significance of the research study is also portrayed in the chapter. In carrying out research, there are delimitations and limitations in which these are discussed clearly on how they affect the research study, the summary being the last sub heading of the chapter.